Direct Modulation Performance of Quantum Well Semiconductor Laser Diodes Operating in Multimode (Dhaka University Journal of Applied Science and Engineering, 2022)
A theoretical investigation has been carried out for both the direct sinusoidal modulation and associated noise performance of InGaN based quantum well (QW) semiconductor laser diodes (LDs) operating in multimode. The study is based on the QW lasers with two separate quantum wells with different carrier injection ratios. A model of multimode rate equations is developed by taking into account both symmetric and asymmetric cross-gain saturation. Numerical simulation shows that the mode partition effect exists in both the modulated and unmodulated LDs. From modulation at microwave frequency, highly synchronized oscillation of the modes resulting periodic pulse-like output is observed that contains peaks at modulation frequency and its harmonics. Associated total RIN and modal RIN values suppress with the modulation index. The simulation results have well correspondence with the previously reported theoretical and experimental findings.DUJASE Vol. 6 (2) 94-98, 2021 (July)